The Influence of Representativeness on Investment Decision Through Overconfidence - Fitri, Hery Kharisma; Cahyaningdyah, Dwi (Universitas Negeri Semarang, 2021)
This study aims to explore the effect of representativeness on investment decisions through overconfidence as an intervening variable on investors from the Faculty of Economics, Universitas Negeri Semarang. The data used in this study is primary data with a survey method using a questionnaire. The research sample was taken using convenience sampling technique with a sample of 115 investors. The sample was then analyzed using the Partial Least Square (PLS) method with the help of the SmartPLS 3.0 application. The empirical results of this study explain that representativeness has no effect on investment decisions, overconfidence has a significant positive effect on investment decisions, representativeness has a significant positive effect on overconfidence, and overconfidence mediates the relationship between representativeness and investment decisions in full mediating.